The Effect Of Budget On Financial Performance Accountability (Study On Bkad Enrekang Regency) - Rahmawati (JEKAMI Journal of Accounting, 2021)
This research will be conducted in Enrekang and located at the Regional Finance and Assets Agency (BKAD) office of Enrekang Regency, which aims to determine the effect of budget on performance accountability (study on BKAD of Enrekang Regency). Then this study uses descriptive analysis research methods and quantitative approaches, then the author uses several data collection techniques, namely Field Studies, Literature Studies and Data Analysis Techniques used in this study are: Data Quality Test, Classical Assumption Test, Simple Linear Regression Analysis, Hypothesis Testing (Partial Test (t Test)) and Coefficient of Determination Test (R2). The results of research and discussion on the effect of budgeting on performance accountability (Study on BKAD of Enrekang Regency), the authors can draw the following conclusions: Based on the results of the study, the value of t-count = 3,018. Where the results of the t distribution table obtained a t-table value of 1.688. So it can be concluded that t-count > t-table ( 3.018 > 1.688 ) in other words the budget has a significant effect on performance accountability.